Adolescents and adults at clinical high-risk for psychosis: age-related differences in attenuated positive symptoms syndrome prevalence and entanglement with basic symptoms. Issue 5 (16th December 2015) - Gerstenberg, M.; Theodoridou, A.; Traber-Walker, N.; Franscini, M.; Wotruba, D.; Metzler, S.; Müller, M.; Dvorsky, D.; Correll, C. U.; Walitza, S.; Rössler, W.; Heekeren, K.
Abstract : Background: The attenuated positive symptoms syndrome (APSS) is considered an at-risk indicator for psychosis. However, the characteristics and developmental aspects of the combined or enriched risk criteria of APSS and basic symptom (BS) criteria, including self-experienced cognitive disturbances (COGDIS) remain under-researched. Method: Based on the Structured Interview of Prodromal Syndromes (SIPS), the prevalence of APSS in 13- to 35-year-old individuals seeking help in an early recognition program for schizophrenia and bipolar-spectrum disorders was examined. BS criteria and COGDIS were rated using the Schizophrenia Proneness Instrument for Adults/Children and Youth. Participants meeting APSS criteria were compared with participants meeting only BS criteria across multiple characteristics. Co-occurrence (APSS+/BS+, APSS+/COGDIS+) was compared across 13–17, 18–22 and 23–35 years age groups. Results: Of 175 individuals (age = 20.6 ± 5.8, female = 38.3%), 94 (53.7%) met APSS criteria. Compared to BS, APSS status was associated with suicidality, higher illness severity, lower functioning, higher SIPS positive, negative, disorganized and general symptoms scores, depression scores and younger age (18.3 ± 5.0 v. 23.2 ± 5.6 years, p < 0.0001) with age-related differences in the prevalence of APSS (ranging from 80.3% in 13- to 17-year-olds to 33.3% in 23- to 35-year-olds (odds ratio 0.21, 95% confidence interval 0.11–0.37). Within APSS+ individuals, fewer adolescents fulfilled combined risk criteria of APSS+/BS+ or APSS+/COGDIS+ compared to the older age groups. Conclusions: APSS status was associated with greater suicidality and illness/psychophathology severity in this help-seeking cohort, emphasizing the need for clinical care. The age-related differences in the prevalence of APSS and the increasing proportion of APSS+/COGDIS+ may point to a higher proportion of non-specific/transient, rather than risk-specific attenuated positive symptoms in adolescents.